Patent blue V dye anaphylaxis: a case report and literature review - Costa,Diogo (2020)
Abstract Background: Anaphylaxis is a constant perioperative concern due to the exposure to several agents capable of inducing hypersensitivity reactions. Patent blue V (PBV), also known as Sulfan Blue, a synthetic dye used in sentinel node research in breast surgery, is responsible for 0.6% of reported anaphylactic conditions. We present a case of a 49-year-old female patient who underwent left breast tumorectomy with sentinel lymph node staging using PBV and experienced an anaphylactic reaction. Methods: We conducted a literature search through PubMed for case reports, case series, review and systematic reviews since 2005 with the keywords “anaphylaxis” and “patent blue”. We then included articles found in these publications’ reference sections. Results: We found 12 relevant publications regarding this topic. The main findings are summarized, with information regarding the clinical presentation, management, and investigation protocol. Hypotension is the most common clinical manifestation. The presentation is usually delayed when compared with anaphylaxis from other agents and cutaneous manifestations are occasionally absent. Patients may have had previous exposure to the dye, used also as a food, clothes and drug colorant. Conclusion: The diagnosis of anaphylaxis in patients under sedation or general anesthesia may be difficult due to particularities of the perioperative context. According to the published literature, the presentation of the reaction is similar in most cases and a heightened clinical sense is key to address the situation appropriately. Finding the agent responsible for the allergic reaction is of paramount importance to prevent future episodes.